A comparison between multi-proxy and historical data of drift-ice conditions on the East Greenland shelf - NSF Arctic Data Center (Arctic Data Center, 2015)
The reduction in sea ice along the SE Greenland coast during the last century has severely impacted ice-rafting to this area. In order to reconstruct ice-rafting and oceanographic conditions in the area of Denmark Strait during the last ~150 years, we conducted a multiproxy study on three short (20 cm) sediment cores from outer Kangerdlugssuaq Trough (~300 m water depth). The proxy-based data obtained have been compared with historical and instrumental data to gain a better understanding of the ice sheet-ocean interactions in the area. A robust chronology has been developed based on 210Pb and 137Cs measurements on core PO175GKC#9 (~66.2°N, 32°W) and expanded to the two adjacent cores based on correlations between calcite weight percent records. Our proxy records include sea-ice and phytoplankton biomarkers, and a variety of mineralogical determinations based on the <2 mm sediment fraction, including identification with quantitative x-ray diffraction, ice-rafted debris counts on the 63-150 µm sand fraction, and source identifications based on the composition of Fe oxides in the 45-250 µm fraction. A multivariate statistical analysis indicated significant correlations between our proxy records and historical data, especially with the mean annual temperature data from Stykkishólmur (Iceland) and the storis index (historical observations of sea-ice export via the East Greenland Current). In particular, the biological proxies (calcite weight percent, IP25, and total organic carbon %) showed significant linkage with the storis index. Our records show two distinct intervals in the recent history of the SE Greenland coast. The first of these (ad 1850-1910) shows predominantly perennial sea-ice conditions in the area, while the second (ad 1910-1990) shows more seasonally open water conditions.